Perancangan Program Aplikasi Penentuan Portofolio Investasi dengan Metode Dempster Shafer Fuzzy-Analytical Hierarchy Process - Rojali Rojali; Syaeful Karim; Edgar Gerriano (Bina Nusantara University, 2011)
Investment is very popular nowadays to gain profits of the available property. Many investment portfolios are available but there are still a handful of users who have not been able to determine the best type of investment. Surely it would be very unfortunate if the property can not be well invested. Therefore, it is necessary to propose another alternative method that can determine the existing investment portfolio. This method begins by a process which details existing factors in every investment portfolio. Then, it takes intuition properly to give weight to the initial calculation. After that, it takes a Fuzzy concept as a tool to provide a numerical weight to each of the parameters. The final step is weighting process using Dempster Shafer method. With the use of three basic concepts, investors are expected to obtain objective and optimal computing results related to the profitable investment portfolio selection.